Jangan bersedih, karena allah selalu bersamamu / Mahmud Al-Mishri; Penerjemah, M. Alaika Salamulloh; Editor, Ahmad Saifuddin - MAHMUD al-Mishri; ALAIKA Salamulloh; AHMAD Saifuddin (Diva Press, 2011)
228 hlm. ; 20 cm.